Given that the function g(x)=x-3/x+4, the evaluation gives:
- g(9) = 6/13.
- g(3) = 0.
- g(-4) = undefined.
- g(-18.75) = 1.07.
- g(x+h) = x+h-3/x+h+4
<h3>How to evaluate the function?</h3>
In this exercise, you're required to determine the value of the function g at different intervals. Thus, we would substitute the given value into the function and then evaluate as follows:
When g = 9, we have:
g(x)=x-3/x+4
g(9) = 9-3/9+4
g(9) = 6/13.
When g = 3, we have:
g(x)=x-3/x+4
g(3) = 3-3/3+4
g(3) = 0/13.
g(3) = 0.
When g = -4, we have:
g(x)=x-3/x+4
g(-4) = -4-3/-4+4
g(-4) = -1/0.
g(-4) = undefined.
When g = -18.75, we have:
g(x)=x-3/x+4
g(-18.75) = -18.75-3/-18.75+4
g(-18.75) = -15.75/-14.75.
g(-18.75) = 1.07.
When g = x+h, we have:
g(x)=x-3/x+4
g(x+h) = x+h-3/x+h+4
Read more on function here: brainly.com/question/17610972
#SPJ1
Answer:
Step-by-step explanation:
Answer:
What equation? Please include the equation
Answer:
Less close to one
Step-by-step explanation:
0.006/6,000= 0,000001
Answer:
The system has one solution
Step-by-step explanation:
we have the system of equations
----> equation A
----> equation B
Solve the system by substitution
substitute equation A in equation B
Solve for x
Multiply by 3 both sides to remove the fraction
Combine like terms
![x=-\frac{6}{10}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B6%7D%7B10%7D)
Simplify
![x=-\frac{3}{5}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B3%7D%7B5%7D)
<em>Find the value of y</em>
![y=\frac{2}{3}(-\frac{3}{5})+2](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7B3%7D%28-%5Cfrac%7B3%7D%7B5%7D%29%2B2)
![y=-\frac{6}{15}+2](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B6%7D%7B15%7D%2B2)
![y=\frac{24}{15}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B24%7D%7B15%7D)
Simplify
![y=\frac{8}{5}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B8%7D%7B5%7D)
The solution of the system is the point ![(-\frac{3}{5},\frac{8}{5})](https://tex.z-dn.net/?f=%28-%5Cfrac%7B3%7D%7B5%7D%2C%5Cfrac%7B8%7D%7B5%7D%29)
therefore
The system has one solution